Construction Managers' Perception of the Factors Affecting Sustainability in Construction Projects - Taheriattar, Reza; Farzanehrafat, Morvarid (International Journal of Sustainable Construction Engineering and Technology, 2014)
Sustainable construction is a comprehensive concept which requires long-term planning. Moreover, construction managers play a key role in leading, planning and scheduling of a construction project. As a result, sustainability of construction projects can be affected by construction managers’ decisions. In addition, for greater development of sustainable construction, affecting factors should firstly be notified. Therefore, it seems necessary to investigate construction managers’ perception of the factors affecting sustainability in construction projects. To quantify managers’ perspective of construction sustainability, a survey involving 15 construction managers from Iran construction industry was employed. A statistical comparative analysis used to identify the most important factors affecting sustainability performance at project-level. The results show that most of the factors affecting sustainable construction can be addressed by management teams. The findings will be useful for managers to improve construction sustainability performance at project-level.